Carnival of souls - Harvey, Herk, 1924-1996; Clifford, John, 1918-2010; Hilligoss, Candace; Harcourt Productions; Cinetel Films ([Los Angeles, CA] : Harcourt Productions, 1962)
Mary Henry is riding around in a car with two friends when they are forced off of a bridge. It appears that all are drowned, until Mary, quite some time later, amazingly emerges from the river. After recovering, Mary accepts a job in a new town as a church organist, only to be dogged by a mysterious phantom figure that seems to reside in an old run-down pavilion. --
Originally released as a motion picture in 1962.
Candace Hilligoss, Frances Feist, Sidney Berger, Art Ellison, Stan Levitt, Tom McGinnis, Forbes Caldwell, Dan Palmquist, Bill De Jarnette.
Cinematographer, Maurice Prather; editors, Dan Palmquist, Bill De Jarnette; music, Gene Moore.
In English; also available an Spanish dubbed version.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015).
Keywords: Carnivals -- Drama; Ghost plays; Drag racing -- Drama; Lawrence (Kan.); Horror films; Feature films; Internet videos; Streaming video